Introduction: Future of the Flint Hills (Symphony in the Flint Hills, 2016)
Each year, thousands of bicyclists flock to the Flint Hills to test their mental and physical endurance in a 200-mile extreme race known as the world’s premier gravel grinder. In 2015, when record rainfalls transformed gravel roads into quicksand, the race lived up to its name “Dirty Kanza.”
Keywords: Flint Hills; future; GRASSLANDS – WIND IN THE BLUESTEM; Chris Wolf Edmonds